GINAN URDU POETRY: THE OLDEST AVAILABLE URDU LITERATURE - Dr. Muhammad Irfan Ahsan Pasha; Dr Rukhsana Bibi (Zaban-o-Adab, 2022)
URDU language posesses many theories about its emergence Due to the absence of solid evidances.To a large extant political and social realities have been explored. Although the lingual soureces are being discovered even today.Some critics said Wali Daccni the Bawa Adam ofUrdu and others extended the roots of Urdu literature to AmirKhusro and Masood Saad Salman. This article proves that contrary tothe well established theory that Amir Khusro’s poetry is the oldest available in Urdu, there is even the Ismaili Ginan poetry which has a background through the tenth century and due to religious esteem its has lesser chances of impurity. So it holds a more authentic status.Exploration of Ginan poetry provides linguistic evidance and authentic oldest text to lighten the history of Urdu literature to centuries back as known earlier.